Predation of the Buffy-fronted Seedeater Sporophila frontalis (Aves: Emberizidae) on Merostachys neesii (Poaceae: Babusoideae) seeds during a masting event in the Atlantic forest - Cestari, Cesar [UNESP]; Bernardi, Claudio Joao [UNESP] (Revista Biota Neotropica, 2011)
The Buffy-fronted Seedeater Sporophila frontalis (Verreaux, 1869) is frequently found foraging on seeds during ephemeral masting events of bamboos in the Atlantic forest. In the present study, we analyzed the predation activity of S. frontalis on seeds of Merostachys neesii Rupr. during a masting event in an Atlantic forest reserve on southeastern Brazil. We conducted point counts in spots with M. neesii and in spots without bamboos along trails to determine the presence of S. frontalis on M. neesii clumps. Additionally, focal observations on bamboo clumps and seed traps were used to verify the predatory impact of S. frontalis on M. neesii seeds. S. frontalis was present in 6 out 18 point counts in M. neesii clumps. The seedeater behaved territorially in bamboo clumps and presented a mean predation rate of 1.10 bamboo seeds/minute. Seed traps had up to 80% of the seeds predated. The large amount of seeds available during bamboo masting events probably contributes to the maintenance of wandering populations of S. frontalis in the Atlantic forest. on the other hand, the predation of seeds by S. frontalis may reduce the reproductive germination and the propagation of the bamboos whose growth may in turn negatively affect the establishment of other forest species.

O pixoxó Sporophila frontalis (Verreaux, 1869) é freqüentemente encontrado forrageando em sementes durante eventos de frutificação em massa de bambus na floresta Atlântica. No presente estudo, nós analisamos a atividade de predação de S. frontalis em sementes de Merostachys neesii Rupr. durante um evento de frutificação em uma reserva da floresta Atlântica no sudeste do Brasil. Nós conduzimos pontos de contagem em locais com M. neesii e em locais sem bambus ao longo de trilhas para determinar a presença de S. frontalis em touceiras de M. neesii. Adicionalmente, observações focais e coletores de sementes foram utilizados em touceiras de M. neesii para verificar o impacto de predação em sementes realizado pelo pássaro. Sporophila frontalis esteve presente em 6 de 18 pontos de contagem com touceiras de M. neesii. Esta espécie se comportou territorialmente em touceiras de bambu e apresentou uma taxa de predação média de 1.10 sementes/minuto. Os coletores de sementes possuíram até 80% das sementes predadas. Provavelmente, a enorme quantidade de sementes disponíveis durante eventos de frutificação em massa de bambus contribuem para a manutenção de populações vagantes de S. frontalis na floresta Atlântica. Por outro lado, a predação de sementes por S. frontalis pode reduzir a germinação reprodutiva e a propagação de bambus, cujo crescimento interfere negativamente no estabelecimento de outras espécies de plantas arbóreas.
Predação do pixoxó Sporophila frontalis (Aves: Emberizidae) em sementes de Merostachys neesii (Poaceae: Babusoideae) durante um evento de frutificação em massa na floresta Atlântica
Keywords: bamboos; bird-plant interaction; Emberizidae; foraging behavior; predation rate